Thermal generalist behaviour of invasive Puccinia striiformis f. sp. tritici strains under current and future climate conditions. (8th March 2018) - de Vallavieille‐Pope, C.; Bahri, B.; Leconte, M.; Zurfluh, O.; Belaid, Y.; Maghrebi, E.; Huard, F.; Huber, L.; Launay, M.; Bancal, M. O.
Abstract : Yellow rust is a devastating wheat disease. Since 2000, Puccinia striiformis f. sp. tritici strains PstS1 and PstS2 have become adapted to high temperatures and have spread worldwide. By 2011, Warrior strains had invaded both warm and cold areas of Europe. This study questioned whether thermal aptitude promoted the spread of Warrior strains, similar to PstS1/PstS2, by comparing infection efficiency (IE) at five temperatures and latent period (LP) under warm and cold regimes for Warrior isolates and pre‐2011 reference strains on two susceptible wheat varieties. The Warrior isolates showed a range of IE and LP responses to temperature that was intermediate between the northern reference isolates adapted to cold conditions and both the southern and invasive PstS2 isolates adapted to warm conditions. Warrior isolates had the highest IE under optimal temperatures of 10 and 15 °C, and displayed reduced infectivity under the warmest (20 °C) and coldest (5 °C) temperatures. Warrior strains acted as thermal generalists and the reference isolates acted as specialists. An IE thermal response was used to simulate the development of each isolate under future climate scenarios in a temperate and Mediterranean region. Isolates had the same ranking for yearly IE over the three 30‐year periods (1971–2000, 2021–2050, 2071–2100) and both locations, with a slight infection increase in the future. However, in the future IEs increased in earlier months. The thermal generalist profile of Warrior isolates for IE was confirmed, with an intermediate capacity to tolerate warming climate, whereas the southern isolates are better adapted to warm conditions, but do not have the virulences necessary to develop on current varieties.